Direct conversion of aromatic amides into crystalline covalent triazine frameworks by a condensation mechanism - Yu, Soo-Young; Kim, Jin Chul; Noh, Hyuk-Jun; Im, Yoon-Kwang; Mahmood, Javeed; Jeon, In-Yup; Kwak, Sang Kyu; Baek, Jong-Beom (Cell reports physical science, 2021)
Multiple studies have recently been conducted to develop well-ordered covalent triazine-based frameworks (CTFs). To date, few studies have demonstrated CTFs with high crystallinity using novel synthesis strategies and different building blocks. To construct highly crystalline CTFs with enhanced performance, significant technical advancements in fundamental chemical insights are essential. Here, we report that the phosphorus pentoxide (P2O5)-catalyzed condensation of biphenyl-based amide and nitrile monomers can produce ordered pCTF-2. The pCTF-2A directly synthesized from amide monomers showed unusually higher crystallinity and porosity than the pCTF-2N synthesized from nitrile monomers. Based on experimental results, density functional theory (DFT) calculations revealed that amide groups can be directly trimerized into triazine rings in the presence of P2O5, which is a more thermodynamically favorable reaction than those from nitrile groups. Based on this mechanistic insight, the efficient and better synthesis strategy provides an effective pathway for the formation of crystalline CTFs. [Display omitted] •Synthesis of an ordered covalent triazine framework (pCTF) directly from amide monomers•Mechanistic pathway proposal for the synthesis of pCTFs from amide monomers•High performance of ordered pCTFs with well-defined micropores To expand monomer availability and synthetic pathways, Yu et al. present the syntheses of covalent triazine frameworks (pCTFs) using both amide and nitrile monomers in the presence of phosphorus pentoxide as a catalyst. They present a highly ordered pCTF-2 structure with well-defined micropores constructed from the direct condensation of amide monomers.